The effect of teaching emotion-oriented processing strategies on the perceived stress of cyberbullied medical students - Narges Mirani Sargasi; Akram Hafezi; Ahmad Mirgol; Tayebeh Shamsaei Zafarghandi; Milad Khani; Maryam Tariq Tayyeb (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  Cyber harassment of students is a significant stressor in today's society. Medical students are responsible for the physical health of people in the future, so paying attention to their mental health is of enormous importance. Therefore, the purpose of the present study was to investigate the effect of teaching emotion-oriented processing strategies on the perceived stress of cyberbullied medical students. Materials & Methods: The present research was a quasi-experimental study that was conducted on medical students of Mashhad University of Medical Sciences in the academic year of 2022-2023. Thirty cyber-damaged medical students who had been cyberbullied and perceived stress were selected by the purposive sampling method and randomly divided into experimental and control groups. The educational intervention included 9 sessions, an hour for each session, virtually through the Skyroom platform. Before and after the intervention, participants filled out demographic and Perceived Stress Scale (PSS) data collection forms. The statistical test consisted of the ANOVA, which was analyzed by SPSS V.25, and the level of significance was considered less than 0.05. Results: The mean and standard deviation of the perceived stress scores among medical students who suffered from cyberbullying in the post-test of the experimental groups decreased compared to the control group (P=0.003). Based on the covariance analysis, there was a significant difference in the perceived stress scores of the experimental group compared to the control group (P<0.038). Conclusion: The use of emotion-oriented processing by the cyberbullied medical students can improve their perceived stress.